Analysis of Defamation on Social Media - Suwinto Johan (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
This study examines defamation on social media, which has become more prevalent with the rapid growth of digital platforms and applications. It adopts a normative approach using primary and secondary legal sources. Informing others that a person failed to pay for ordered and consumed food is generally a civil matter. However, publishing a video that clearly identifies the individual may constitute defamation, particularly if the claim is inaccurate or later disproven. Such content can harm reputation, especially when accompanied by provocative language that misrepresents the actual situation. This study concludes that posting identifiable and misleading video content on social media may result in legal liability.